Complication rates, failure to rescue and in-hospital mortality after cytoreductive nephrectomy in the older patients. Issue 4 (May 2020) - Palumbo, Carlotta; Knipper, Sophie; Dzyuba-Negrean, Cristina; Pecoraro, Angela; Rosiello, Giuseppe; Tian, Zhe; Shariat, Shahrokh F.; Simeone, Claudio; Briganti, Alberto; Saad, Fred; Berruti, Alfredo; Antonelli, Alessandro; et al.
Abstract: Objectives: Historical data showed worse perioperative outcomes after cytoreductive nephrectomy (CN) in older patients. Additionally, the CARMENA trial questioned the survival benefit of cytoreductive CN. We reassessed complication, failure to rescue (FTR) and mortality rates after CN in a contemporary cohort of older patients with metastatic renal cell carcinoma (mRCC). Materials and Methods: From National Inpatient Sample (NIS) database (2008–2015), mRCC patients treated with CN were abstracted. Univariable and multivariable logistic regression models tested for the relationship between age (≤55 vs. 56–70 vs ≥71 years), Charlson Comorbidity Index (CCI) and modified Frailty Index (mFI) categories and complications, FTR and in-hospital mortality. All models were clustered, weighted and adjusted for all available patient and hospital characteristics. Results: Of 3644 mRCC patients treated with CN, 924 (25.4%) were ≥ 71 years old, 435 (11.9%) had CCI ≥ 2 and 749 (20.6%) were frail. In multivariable logistic regression models, age ≥ 71 (odds ratio [OR] 1.4, p  < .001), CCI ≥ 2 (OR 1.88, p < .001) and frail status (OR 1.91, p < .001) were independent predictors of overall complications. Age ≥ 71 was also an independent predictor of FTR (OR 2.27, p  = .04), but not of in-hospital mortality. Both CCI and mFI were not significantly associated with either FTR or in-hospital mortality. Conclusion: Older patients with mRCC are more likely to experience higher rates of overall complications, FTR and in-hospital mortality following CN. These results highlight the importance of rigorous selection criteria for older surgical candidates. Moreover, timely recognition and rapid response to complications are particularly critical in this population.